Optimalisasi Kesadaran Kesehatan Warga Desa Sarirogo dengan Sosialisasi Hidup Sehat dan Implementasi Medical Check-up - Budi Prabowo; Aldino Maulana Albar; Roikhan Salim (FUNDAMENTUM : Jurnal Pengabdian Multidisiplin, 2024)
This study aims to thoroughly explore the role of medical check-ups in maintaining the basic physical health of the residents of Sarirogo Village, with a particular focus on the prevention of non-communicable diseases, which have been on the rise in the area. The background of this research is based on the fact that there is a high prevalence of non-communicable diseases, such as hypertension, diabetes, and cardiovascular diseases, that often go undetected in their early stages. This is primarily due to a lack of public awareness about the importance of regular health checkups, as well as limited access to adequate healthcare services. As a result, delayed diagnoses exacerbate the overall health conditions within the community. This study employs a qualitative approach using a literature review method to analyze sources from relevant scientific journals. These sources serve as the theoretical foundation to understand the relationship between the frequency of medical check-ups and the prevention of chronic disease progression. The findings of this study highlight the significant role that medical check-ups play in the early detection of various potentially life-threatening health conditions, thereby preventing the development of more serious illnesses. Based on these findings, this research emphasizes the urgent need to enhance the accessibility of regular medical check-up services for the residents of Sarirogo Village, alongside the necessity to raise collective awareness about the benefits of routine health screenings.